Influencia de la gestión gerencial sobre el clima laboral en el restaurante Chilis - Piura 2018 - Guzmán Benites, Thalia Maricel (2019)
This research paper was prepared with the aim of determining the influence of management on the working climate of the workers of the Chili’s restaurant in the city of Piura [ 2018. Considering the current context where the good management of human resources has become one of the main focuses of attention, it is impossible not to look back at the environment or climate that generates the good practice of administration or management within the restaurant. So, the focus of the thesis was on the interest to determine How does management influence the working climate in the restaurant CHILIS- PIURA 2018? The study was developed using cross-sectional research design. The sample was made up of the total population corresponding to 35 questions and the second that evaluates the work climate with 38 questions, qualified by Likert’s 5-point scale. With regard to data analysis, tables were used, as well as statistical graphs; in addition to the analysis using descriptive and causal inferential statistics for the respective processing of information. Finally, according to the results obtained, it is concluded that management has a moderate positive influence on the working climate of the Chili’s restaurant in the city of Piura in 2018.